Praktik Pendampingan Perkara Non Litigasi Mediasi Sengketa Tanah Pada Lembaga Bantuan Hukum Ansor - Farchan Hamdani; R. Fahrurrozi Nur Ansori (Lembaga Pengembangan Kinerja Dosen, 2025)
Non-litigation legal assistance in land dispute resolution is carried out by the Ansor Legal Aid Institute (LBH Ansor). This assistance is crucial considering the complexity of land law and the high demand of the community, especially vulnerable groups, for access to fast, efficient, and low-cost conflict resolution. This research is driven by the low public understanding of non-litigation mechanisms and the challenges in realizing proportional access to justice. The main objective is to comprehensively document the assistance procedures and identify the applied advocacy model. This research method uses a normative legal approach with a statute approach and a conceptual approach. The results of this study describe that LBH Ansor plays a strategic role as a mediator and legal facilitator, which includes initial case assessment, preparation of a mediation framework, and assistance in negotiations between the disputing parties. The main findings show that LBH Ansor's non-litigation assistance practices have successfully increased the effectiveness of land dispute resolution by prioritizing the principles of restorative justice and peace agreements, while also providing a replicable model for increasing access to justice outside the courts.